(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Banks manage individuals’ most fluid resource (money), and run a country’s economy. The banking system in India is fundamentally not the same as that of different countries due to the countries one of a kind financial, social and geographic attributes. India has an extensive population and land estimate, a differing culture, and outrageous aberrations in income, which are set apart among its districts. There are elevated amounts of absence of education among a substantial percentage of its population at the same time in the meantime, the country has an extensive supply of administrative and technologically propelled gifts. The country’s financial policy structure consolidates communist and capitalistic highlights with an overwhelming inclination towards public sector venture. This paper researches the technical efficiency of real agents of Indian commercial banks. For this reason, the data envelopment analysis (DEA) model was utilized with four info variables (viz. Deposits, Interest costs, Operating costs, Assets) and four yield variables advances and advances, investments, net interest income, and non-interest income. DEA is a nonparametric technique for estimating the efficiency of a Decision Making Unit